2011
DOI: 10.1002/adfm.201101103
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electronic Properties of Semiconductor‐Sensitized Solar‐Cell Interfaces

Abstract: A recent study has reported a power‐conversion efficiency of 5.1% for solar cells employing mesoporous TiO2 films sensitized with quantum dots of stibnite (Sb2S3). Here, a first‐principles atomic‐scale investigation of the interface between TiO2 and Sb2S3 is presented. The proposed atomistic interface model is free of defects, and the calculated energy‐level alignment at the interface indicates that the ideal open‐circuit voltage is as high as 1.6 V. Films sensitized with the isostructural compounds bismuthini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
93
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 59 publications
8
93
0
Order By: Relevance
“…So far, much focus has been placed on the synthesis and electronic properties [12][13][14][15] of Sb 2 S 3 . To complement these known aspects, we present here a study of the lattice vibrational properties of Sb 2 S 3 using density-functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…So far, much focus has been placed on the synthesis and electronic properties [12][13][14][15] of Sb 2 S 3 . To complement these known aspects, we present here a study of the lattice vibrational properties of Sb 2 S 3 using density-functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…Like CdTe, but in contrast with CIGS and CZTS, Sb2Se3 is a simple binary compound with fixed phase and stoichiometry. It has a very strong absorption coefficient (>10 5 cm -1 at short wavelengths) and its bandgap is ~1.1 eV 17,18 , optimal for single-junction solar cells. The constituents of Sb2Se3 are non-toxic and low in cost (Sb has similar cost to Cu), and, as we proceed to show herein, Sb2Se3 films are produced using minimal energy, enabling in principle a low energy-payback time for a solar cell 19 .…”
mentioning
confidence: 99%
“…Besides, the relative positions of the conduction band edges of nanostructured Sb 2 Se 3 and SnO 2 display favourable energetics for electron transfer at their interface [12]. In addition, theoretical calculations performed by Giustino et al [9,10] demonstrated the improved performance of Sb 2 Se 3 -based devices compared to Sb 2 S 3 based cells, and suggested Sb 2 Se 3 as a promising candidate for achieving 20 % PCE. In spite of these advantages, Sb 2 Se 3 -based solar cells have rarely been experimentally demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Among these materials, antimony selenide (Sb 2 Se 3 ) is a group V 2 -VI 3 layered structured direct band gap semiconductor with orthorhombic crystal structure [7]. Sb 2 Se 3 displays a narrow band gap of 1.1-1.3 eV, [8][9][10] which approaches the ideal Shockley-Queisser value, [11] and has the ability to extend light harvesting over the near-IR region up to approximately 1000 nm. Besides, the relative positions of the conduction band edges of nanostructured Sb 2 Se 3 and SnO 2 display favourable energetics for electron transfer at their interface [12].…”
Section: Introductionmentioning
confidence: 99%